Riding into myth: Manifest Destiny, Nietzschean ethics and the creation of a new western frontier mythology in Cormac McCarthy's Blood Meridian - Edley, Christopher (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2017)
Cormac McCarthy's Blood Meridian or the Evening Redness in the West is a provocative evocation of the American West that has attracted a wide range of critical responses. This study has three foci: the novel as epic myth, McCarthy's critique of Manifest destiny, and the influence of Nietzschean philosophy on the judge and McCarthy's portrayal of the human condition. These concerns conduce to an alternative reading of the conclusion of the novel. Blood Meridian is a unique textual enterprise as it both conforms to and subverts mythic conventions associated with both Classical epic and the American West. Recognition of the resonances between Blood Meridian and these mythologies helps the reader to engage with McCarthy's ambitious creation of a powerful literary allegory in the tradition of Twain and Faulkner. Having situated McCarthy's enterprise within these co-ordinates, the study then moves on to examine the novel's stunning critique of Manifest Destiny, in the context of the implications that such thinking has had on American foreign policy over the past two centuries, and that continue to inspire American involvement in military conflicts well into the twenty-first century. The final area of focus is the influence of Friedrich Nietzsche's philosophy on the character of the judge and the weltanschauung that the novel presents. McCarthy's ultimate objective is to demonstrate that humankind's most basic condition is an inherently violent one. The more critically accepted reading of the novel is challenged by postulating the kid's triumph over the judge as not only in keeping with the literary tradition of Melville and others but also a logical outcome of the novel's allegory of American military involvement in Vietnam. The study concludes that whilst McCarthy has gone on to receive critical acclaim and public praise for works published after Blood Meridian, this work remains both his artistic masterpiece and his most far-reaching engagement with issues of eschatological and political importance. It is argued that, given the contemporary escalation in geo-political tensions, Blood Meridian may well continue to provide insight into the nature of American domestic and foreign policy for decades to come.
Keywords: McCarthy, Cormac, 1933-. Blood meridian; Nietzsche, Friedrich Wilhelm, 1844-1900 -- Influence; Mythology in literature; American fiction -- 20th century -- History and criticism; West (U.S.) -- In literature